ShinyGO: a graphical gene-set enrichment tool for animals and plants - Ge, Steven Xijin; Jung, Dongmin; Yao, Runan (Bioinformatics, 2020)
Abstract Motivation Gene lists are routinely produced from various omic studies. Enrichment analysis can link these gene lists with underlying molecular pathways and functional categories such as gene ontology (GO) and other databases. Results To complement existing tools, we developed ShinyGO based on a large annotation database derived from Ensembl and STRING-db for 59 plant, 256 animal, 115 archeal and 1678 bacterial species. ShinyGO’s novel features include graphical visualization of enrichment results and gene characteristics, and application program interface access to KEGG and STRING for the retrieval of pathway diagrams and protein–protein interaction networks. ShinyGO is an intuitive, graphical web application that can help researchers gain actionable insights from gene-sets. Availability and implementation http://ge-lab.org/go/. Supplementary information Supplementary data are available at Bioinformatics online.